Pulmonary blastomycosis in a professional diver: An occupational risk - Ryan R Kroll; Ronald F Grossman (Canadian Respiratory Journal)
In certain parts of the United States and Canada, and northern Ontario in particular, the dimorphic fungus Blastomyces dermatitidis is endemic and can cause infection in exposed individuals. The site of infection is usually pulmonary, causing respiratory and constitutional symptoms, but can also affect other sites in the body. Symptom severity can vary substantially from no symptoms to fatal acute respiratory distress syndrome. The present report describes a 27-year-old professional diver who had recently worked in northern Ontario, who developed symptoms of pneumonia and exhibited atypical findings on chest imaging. He was diagnosed with blastomycosis based on histopathological findings and fungal culture, and was treated with amphotericin B and itraconazole in accordance with treatment guidelines. While outdoor occupations in endemic areas increase the risk of infection, there is no literature specifically identifying professional diving as an occupational risk for blastomycosis.